Pro-p groups with few relations and universal Koszulity - Quadrelli, Claudio (Mathematica Scandinavica, 2021)
Let p be a prime. We show that if a pro-p group with at most 2 defining relations has quadratic F_p-cohomology algebra, then this algebra is universally Koszul. This proves the “Universal Koszulity Conjecture” formulated by J. Mináč et al. in the case of maximal pro-p Galois groups of fields with at most 2 defining relations.